The role of Local wine administration bodies in creating social and cultural capital and in the preservation of local identity - Tóth, Réka (Acta Agraria Debreceniensis, 2008)
the target for the European Union to make Europe the most competitive and dynamic knowledge-based economy in the world. In this process, the education and training are of great importance for the member states. The restructuring of higher education, the modernization of the universities cannot be achieved without new financial resources. They should be ensured by increasing contribution of the private sector. However it is not enough to invest sufficient funds in the educational and training system, they must be expended efficiently. The free higher education itself doesnot necessarily guarantee the equal access and maximal participation. The quality of higher education and equal opportunity can be improved, if the rising funds are expended on infrastructure development and creating an efficiently working student support system.Quality, equal opportunity, efficiency – they are the most important views for the decision-makers in the higher education reform. In my paper, I would like to interpret definitions relating to higher education and in this way I attempt to evaluate the financing systems of the Hungarian higher education formed since the change of the regime, with special regards to the normative financial system combined with the payment of tuition fees. For classification, it is necessary to present the different basic financial models. Furthermore, on the basis of the above criteria, I try to make recommendations on how to improve the present financial model in order to achieve the Lisbon objectives.The topic is important in our days, because tuition fees will be introduced in Hungary from 2008. The problem is very complex, although the analysts in most cases tend to approach the topic with prejudice, depending on their financial and political interests. My analysis may contribute to discernment in the tangle of the pros and cons.